Building an evaluative culture for effective evaluation and results management - Mayne, J. (2008)
A weak evaluative culture undermines many attempts at building an effective evaluation and results management regime. This brief outlines practical actions that an organization can take to build and support an evaluative culture, where information on performance is deliberately sought in order to learn how to better manage and deliver programmes and services. Such an organization values empirical evidence on the results it is seeking to achieve.